Investigating Effects of Topography, Soil and Climate Factors on Soil Organic Carbon Storage in Drylands of Kermanshah Province - Athar Kaveh; Mohammad Hossein Mahdian; Yahya Parvizi; Reza Sokouti Oskouei; Mohammad Hasan Masihabadi (مدیریت بیابان, 2014)
Soil carbon sequestration and storage is one of the important methods to reduce the atmospheric carbon dioxide and mitigating climate change effects. Therefore, with identification of the effective factors on carbon storage can be helpful to improve soil fertility and environmental protection. Therefore, this study was conducted to investigate the effects of some soil physical factors on soil organic carbon (SOC) storage content in drylands of Sarfiroozabad watershed, Kermanshah province, Iran. So, the watershed was separated into homogeneous zones and soil sampling was performed using a randomized systematic method in the units. The samples were transported to the laboratory and texture, TNV%, gravel% and organic carbon were analyzed to determine the SOC storage. Then, using stepwise regression, cluster and factor analysis, the effective factors on carbon storage were studied. The results of cluster analysis showed three variables such as TNV%, Silt% and SP%, are effective on SOC storage and the regression model with this three variables can predict 33 percent of the soil carbon storage variability with a correlation coefficient of 0.574. Also, cluster analysis to predict the effects of physical factors on carbon storage is important with EF= 0.32. Therefore, it was proven that the soil factors are more effective than climate and topography factors to predict SOC storage. It shows that improving the soil conditions and correct management, to keep soil carbon stocks should be given more attention.